Los valores del pretérito perfecto compuesto y del pretérito perfecto simple en Inquieta companía de Carlos Fuentes - Seljak Adimora, Katja (Vestnik za tuje jezike, 2012)
The article focuses on the contrast between Present Perfect Tense and Past Simple Tense, both in theory and in the literary Hispanic American text Inquieta Companía (2004) by Carlos Fuentes. The typical use of these tenses in Mexican Spanish, some exclusive and others shared with Peninsular Spanish, are presented. The author presents the frequency of these tenses in different Spanish dialects. Although Present Perfect Tense is less used than Past Simple Tense, in the Mexican dialect as well as in Peninsular Spanish, it is not disappearing, but its use is limited.
Keywords: Fuentes, Carlos, 1928-2012; ameriška španščina; mehiška španščina; preteklik; sestavljeni preteklik; nesestavljeni preteklik